Analisis Dinamika Atmosfer Kejadian Banjir Di Bali (Studi Kasus: Kuta, Badung 3 April 2024) - Cekarus, Joseph Damian; Jerremy Mezac Sopacua; Yosafat Donni Haryanto (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
Very heavy rain that causes flooding has an intensity of up to 129 mm/hour in Kuta District, Badung Regency on April 03, 2024 caused by cumulonimbus convective cloud activity. This cloud activity can be analyzed by utilizing Himawari-8 satellite remote sensing with NWP and RGB methods processed with the SATAID application. This study aims to identify very heavy rain in the Kuta District area of Badung Regency which resulted in flooding. This research is an analytical descriptive research that uses secondary data from Himawari-8 satellite remote sensing results, flight documentation analysis, and atmospheric lability index data. The methods used include Numerical Weather Prediction (NWP) and Red-Green-Blue (RGB) analysis to support the identification of extreme weather phenomena. The results of the flight documentation show that there is a lowpressure pattern in the southeast region of Bali and wind turns in the Bali region and convergence in the South Bali sea. Clouds began to form at 21:20 UTC and began to cover and reached its peak at 21:50 UTC. High rainfall conditions are caused by the formation of convective clouds and evenly distributed clouds. With the RGB method, high and thick cumulonimbus clouds were observed. Based on atmospheric lability index data, namely K Index (KI), Lifted Index (LI), Total-totals Index (TTI), Severe Weather Threat Index (SWEAT), and Convective Available Potential Energy Index (CAPE), the value is quite supportive when the very heavy rain occurs. This shows that the analysis using the NWP method, RGB method, and some flight documentation data have compatibility and support each other.